Physical activity and screen time among children and adolescents in Kazakhstan - Kwok Ng; Shynar Abdrakhmanova; Assel Adayeva (University of Novi Sad, Faculty of Sport and Physical Education, 2019)
Evidence is lacking that describe the status of physical activity (PA) behaviours among adolescents in Kazakhstan. The aims of the study are to examine the associations between PA and screen time behaviours (STB) among children and young adolescents in Kazakhstan. Data were pooled from the 2015/16 Childhood Obesity Surveillance Initiative (COSI) study (N=4932, 49.8% girls, mean (age)=8.77 SD (age) =0.68) and the 2017/18 Health Behaviour in Schoolaged Children (HBSC) study (N=4153, 49.3% girls, Mean(age)=12.93 SD (age)=1.64). Both studies carried out a two-stage cluster sample to determine a national representative sample. Parental reported their children's PA levels and weekday STB time in the COSI study. In the HBSC study, young adolescents self-reported their PA levels in the past week and the amount of STB hours including TV viewing during weekdays. Data were analysed through cut-offs based on international recommendations of at least 60 minutes of moderate-to-vigorous PA and no more than two hours of screen time per day. The number of children and young adolescents who met the PA recommendations reduced among children aged 9y (68.1%), to young adolescents aged 11y (35%), 13y (37%) and 15y (31%). Similarly, there was a reduction in the proportion of adolescents who met the STB recommendations between the ages of 9y (75%), 11y (60%), 13y (53%), and 15y (47%). Despite some limitations in the methodologies between the COSI and HBSC surveys, and reporting of behaviours, there is a clear pattern that health promoting activities lowers as children transition into young adolescents.